Multilingual Education in Ukraine: Challenges and Perspectives - Kliuiev, Volodymyr; Anisimova, Alla; Glukhova, Liudmyla (International Dialogues on Education Journal, 2016)
The article deals with the challenges and perspectives for the implementation of multilingual education in Ukraine. In the first part definitional aspects of multilingualism and the difference between multilingualism and polyglotism are shown. Thereafter, the main principles of the Bologna Process in Europe and its special features in the Ukrainian higher-education system are illuminated. Furthermore, the distinguishing features of bilingual and multilingual education are highlighted. The second part (discussions and results) deals with educational experiences with the introduction and implementation of multilingual education in the Department of English Philology at the Faculty of Ukrainian and Foreign Philology and Art in the Oles Honchar Dnipropetrovsk National University (DNU). The authors conclude that multilingual education is a key to success and that co-operative and linguocultural learning promote the development of competent multilingual and intercultural persons and their lifelong learning.